Cross-Asset Portfolio Modeling: A Comparative Study of Symmetrical and Asymmetric Dynamic Methods - Dismas Oktavianto; Robiyanto Robiyanto; Andrian Dolfriandra Huruta (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2025)
This study aims to develop a dynamic portfolio model based on asset class, precious metals, world oil, and dollar index. This study performs a comparative test between the Dynamics Conditional Correlation (DCC) and Asymmetric Dynamics Conditional Correlation (ADCC) to determine the best method in forming a dynamic portfolio. Four big cap companies on the Indonesian stock market (BBCA, BBRI, BMRI, and ASII) are examined in this study. The data used were daily returns for the period of January 2, 1998 – December 31, 2020, analyzed using Dynamics Conditional Correlation (DCC) and Asymmetric Dynamics Conditional Correlation (ADCC). The results of empirical testing suggest that including gold, world oil, and dollar index into the dynamic portfolio might increase the portfolio performance and minimize its risks. The stock-gold portfolios formed by utilizing the DCC and ADCC-GARCH methods outperform those composed of only stock. Gold could act as a financial system stabilizer by mitigating losses in the case of extreme negative market shocks. Stock-WTI portfolios formed by utilizing the DCC and ADCC-GARCH methods also outperform those composed of only stock.